'Boys don't rule us': exploring Rwandan girls with disabilities' resistance to masculine dominance in school. Issue 3 (4th March 2019) - Wallace, Derron; Karangwa, Evariste; Bayisenge, Jeannette
ABSTRACT: This paper explores how economically disadvantaged girls with disabilities resist masculine domination at Rwanda's largest inclusive school, Busengare Secondary. Based on 16 in-depth interviews and 3 focus group interviews with Rwandan girls with disabilities, this study draws on critical feminist perspectives to examine the subjectivities of girls with disabilities marginalised by virtue of their gender, class and disability. The findings reveal that girls with disabilities challenge the enduring power of masculine domination that seeks to limit their leadership and learning in classrooms through two distinct strategies: assertive resistance and subversive resistance. At its core, this paper exposes gendered structures of dominance among young people with disabilities not yet addressed in gender studies and disability studies scholarship in Rwanda.